Blunted cortisol response to psychosocial stress in atopic patients is associated with decrease in salivary alpha-amylase and aldosterone: Focus on sex and menstrual cycle phase. (April 2017) - Hlavacova, N.; Solarikova, P.; Marko, M.; Brezina, I.; Jezova, D.
Highlights: High trait anxiety and unfavorable coping strategy are present in female but not male atopic patients. Changes in personality traits were associated with altered neuroendocrine activation. Atopic patients exhibited insufficient responses of alpha-amylase and aldosterone during stress. Menstrual cycle modified alpha-amylase activity in healthy women, but not in patients with atopy. Abstract: A decreased responsiveness of the hypothalamic-pituitary-adrenocortical axis to stress stimuli in patients with atopy is well documented. The aim of this study was to investigate personality traits, salivary alpha-amylase activity and the aldosterone response to psychosocial stress procedure based on public speech in atopic patients with respect to sex and the menstrual cycle (MC) phase. The study was performed in 106 subjects of both sexes, 53 atopic patients suffering from allergic rhinitis, allergic asthma or atopic dermatitis and 53 age-, sex-, the MC phase- and BMI- matched healthy controls. Substantially attenuated activity of alpha-amylase and reduced secretion of aldosterone during the psychosocial stress were observed in the whole sample of patients with atopy. Higher activity of alpha-amylase observed in the follicular compared to the luteal phase in healthy women was not present in atopic patients. In both males and females, atopy was associated with blunted cortisol response but no changes in the heart rate. Psychological characterization revealed a significantly higher trait anxiety and higher preference for avoidance-oriented coping strategy in female but not male atopic patients. These findings provide evidence that patients with atopy exhibit insufficient alpha-amylase and aldosterone responsiveness to psychosocial stress, thus suggesting decreased sympathetic activity. Potential disturbances in sex hormone status during the MC in female patients with atopy have to be considered in future research. Changes in personality traits were demonstrated in female atopic patients, but not in male patients.